Circulating Cell-Free DNA in Pancreatic Head Adenocarcinoma Undergoing Pancreaticoduodenectomy. Issue 2 (February 2021) - Wang, Shin-E; Shyr, Bor-Uei; Shyr, Bor-Shiuan; Chen, Shih-Chin; Chang, Shih-Ching; Shyr, Yi-Ming
Abstract : Objective: Circulating cell-free DNA (cfDNA) analysis is recently reported as a promising prognostic biomarker in various types of cancer. This study aimed to evaluate the role of cfDNA in pancreatic head adenocarcinoma. Methods: Data for pancreatic head adenocarcinoma undergoing pancreaticoduodenectomy were studied for cfDNA. Prognostic factors were determined, and their correlation with cfDNA level was evaluated. Results: The median of cfDNA for 97 cases was 7724 copies/mL, with a mean of 10, 467, and ranging from 1856 to 44, 203. Cell-free DNA was significantly higher in positive lymph node involvement and advanced stage III. Poor prognostic factors included high cfDNA level (>7724 copies/mL), abnormal carbohydrate antigen 19-9, abnormal carcinoembryonic antigen, and advanced stage. The 1- and 5-year survivals for those with high cfDNA were poorer, 70.2% and 21.2%, respectively, as compared with 93.4% and 23.7% for those with low cfDNA level. Only cfDNA level and stage were independent prognostic factors after multivariate analysis. Conclusions: The level of cfDNA was correlated with tumor burden. Therefore, it could be an emerging survival predictor for resectable pancreatic head adenocarcinoma, and its detection might be a promising liquid biopsy to monitor both tumor progression and treatment response.